Orientasi matlamat pencapaian dan keresahan terhadap Bahasa Arab dalam kalangan murid FELDA - Ahmad Termizi, Haryati (2013)
A study was conducted to determine and examine the effectiveness of goal orientation and FELDA student achievement to Arabic Language. The objective of the study was to investigate and compare the level of motivation, confidence and anxiety in the Arabic Language among year five students in FELDA. The objective of this study also shows the relationship between the level of motivation, confidence and anxiety in the Arabic Language achievement. This study was conducted at six different school in FELDA Kota Tinggi which focused of 290 year five students. The selection of the number of samples is based on determining the sample size table Krejcie and Morgan (1970).The instrument used for the survey was adapted from A Study of Anxiety level of Foreign Language Students toward Foreign Language Learning (Wan Zarina et.al, 2007) questionnaire. Data was collected through questionnaires were distributed and analyzed using Statistical Package for Social Sciences version 16.0 which included mean and percentages, t-test and Pearson Correlation. The questionnaire contained 32 items, each one on a 5-point Likert scale ranging from “strongly disagree” (point 1 scale) to “strongly agree” (point 5 scale). The findings show that there is no significant difference between the level of motivation, confidence, and anxiety in the Arabic Language among year five students based on gender. The study also found that there was no significant relationship between the level of motivation, confidence and anxiety in the Arabic language achievement. Therefore efforts should be done to help these students to continue excel in mastering Arabic Language.